2018
DOI: 10.1039/c8cp05350b
|View full text |Cite
|
Sign up to set email alerts
|

Actinide embedded nearly planar gold superatoms: structural properties and applications in surface-enhanced Raman scattering (SERS)

Abstract: Actinide embedded in a gold ring and applications in surface-enhanced Raman scattering (SERS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
3
12
0
Order By: Relevance
“…In a 2D superatom notation it would be the 1S 2 1P 4 1D 4 . The same structure is recovered by Wang et al [11] for the planar or nearly planar An@Au 6 , An=Ac À , Th, Pa + .…”
Section: Introductionsupporting
confidence: 77%
“…In a 2D superatom notation it would be the 1S 2 1P 4 1D 4 . The same structure is recovered by Wang et al [11] for the planar or nearly planar An@Au 6 , An=Ac À , Th, Pa + .…”
Section: Introductionsupporting
confidence: 77%
“…Previous studies have shown that Hirshfeld and VDD charge analyses are reasonable for describing the charge distribution in the clusters with actinide metal atoms. 78,79 The VDD charge is found to be not affected by the calculation functions, which can provide a reliable basis for charge distribution. 71 In addition, Hirshfeld charge analysis has the characteristics of fast calculation speed and strong physical meaning, 80 and it is not affected by the basis set.…”
Section: Bonding Nature Of Anbmentioning
confidence: 89%
“…The fundamental understanding of the chemical bonding nature of actinide (An) materials that have been used in nuclear reactors is necessary for the sustainable development of nuclear energy. Nowadays, most of the studies in the bonding characters for actinides have been focused on two light elements, thorium and uranium, bonded with main group nonmetal elements, due to their relatively substantial quantities and extensive applications. , Systematic studies on actinide compounds involving 5f orbitals in bonding have been widespread across the whole periodic table, such as 5f–5f homometallic An–An bonds; d–5f heterometallic bonding with 3d elements, cobalt, iron, , nickel, copper, zinc; 4d elements, ruthenium, rhodium, , palladium and silver; , 5d elements, rhenium , and platinum; p–5f heterometallic bonding in U-Group 13; , U-Group 14; and An-Group 15 compounds . However, the intermetallic bond between 5f elements and coinage metals remains relatively still less explored either theoretically or experimentally, , let alone the intermetallic bond involving transuranics is particularly in its infancy. Investigating the bonding character of actinide-coinage metals can provide insight into the fundamental understanding of the unusual bonding in these compounds …”
Section: Introductionmentioning
confidence: 99%
“…7,11−18 Systematic studies on actinide compounds involving 5f orbitals in bonding have been widespread across the whole periodic table, such as 5f−5f homometallic An−An bonds; 19−24 d−5f heterometallic bonding with 3d elements, 25−27 cobalt, 28 iron, 29,30 nickel, 31−33 copper, 34 zinc; 35 4d elements, ruthenium, rhodium, 36,37 palladium and silver; 37,38 5d elements, rhenium 39,40 and platinum; 26 p−5f heterometallic bonding in U-Group 13; 41,42 U-Group 14; 43 and An-Group 15 compounds. 44 However, the intermetallic bond between 5f elements and coinage metals remains relatively still less explored either theoretically or experimentally, 45,46 let alone the intermetallic bond involving transuranics is particularly in its infancy. Investigating the bonding character of actinide-coinage metals can provide insight into the fundamental understanding of the unusual bonding in these compounds.…”
Section: Introductionmentioning
confidence: 99%